Thermodynamic model of porosity stabilization in polycrystalline solids. (November 2018) - Klinger, L.; Rabkin, E.
Abstract: We demonstrate that a strong surface segregation of one of the components of the binary polycrystalline material can lead to barrier-less pore formation at the triple and quadruple junctions of the grain boundaries. These pores deplete the bulk of the polycrystal from the segregating component, which can lead to a local minimum in the dependence of the Gibbs free energy of the system on the pore size. We show that in some cases a porous polycrystal can be thermodynamically stabilized. Graphical abstract: Unlabelled Image